JUDÔ PARA IDOSOS: um olhar na perspectiva da saúde coletiva - Melo, Marcelo Galdino de (2024)
This study's theme is the health of the elderly from the perspective of the practice of Judo and its general objective is to understand the practice of Judo for the elderly from the context of collective health. It sets out, as specific objectives, Understanding the context of elderly health in Brazil, based on resulting policies and studies; understand how judo for the elderly has been approached in academic-scientific studies; analyze, from the perspective of the Kodanshas (those who have notorious knowledge of technical, moral and philosophical issues of judo) – who are generally elderly (over 40 years dedicated to the sport), how the practice of judo perceives the elderly and the relationship with health. To this end, as a methodology, the study is characterized as exploratory research, qualitative in nature, using participatory research. Firstly, a large bibliographical research will be necessary and in the second moment, based on the knowledge and experiences acquired in the health field, the proposal is to carry out a participatory research, dialoguing, interviewing and observing, the main references of national judo, known with Kodanshas, with the aim of collectively building an orientation for the practice of judo for elderly people. For the data analysis stage, the Content Analysis method will be used, from the perspective of Bardin (2010). For the discussion on the scenario of the elderly in Brazil, it brings to the discussion the studies of (MORIGUTI and FERRIOLLI, 1998); (CAMARANO and PASINATO, 2004); (NELSON et al. 2007); (VOGEL et al. 2009); (FRAGOSO, 2010); (ANTUNES, 2012); (MINAYO, 2012) and (BRITO et. al. 2013); . Regarding the historical context of Judo, it presents several writings by the founder of Judo Jigoro Kano, as well as (STANLEI, 1994), DELIBERADOR, 1996) and (WEINECK, 1999). of the elderly, based on the authors (MATSUDO et al, 2000); (ALVES, 2001); (FRANCHINI, 2001); (FONSECA, 2004) and (SILVA and PELLEGRINI, 2007). This research chose Judo for the Elderly as its theme, from a Public Health perspective. The organization of the data collected, as well as the readings carried out, made analysis possible, based on the work of gathering key ideas, which in the process of approximation, led us to categories of analysis, leading to an understanding of the organization and functioning of the two themes in isolation, the elderly and the elderly that we work on in exclusive chapters. Judo for the elderly is one of the most effective ways to keep the body active, strengthen muscles and joints... preventing falls, as well as preventing chronic diseases such as diabetes, hypertension and osteoporosis. Furthermore, judo is also an important ally in preventing psychological illnesses, such as depression and anxiety, which can be common in old age, as the sport socializes people. Thus, this great advantage of practicing sports for the elderly is socialization. Participating in group Judo sports activities for seniors can help keep seniors connected to others, strengthening social relationships and reducing isolation, which is important for mental and emotional health. It is necessary to adapt the exercises according to the physical conditions and limitations of each practitioner, to ensure safety during sports practice. In other words, it is extremely important to emphasize that the practice of sports for the elderly must be guided by a Judo professional (Sensei), a black belt graduate and, if possible, also a physical education professional, who will assess physical conditions and individual limitations. of each person, ensuring that the activity is safe and appropriat.